Coupling additive manufacturing and microwave sintering: A fast processing route of alumina ceramics. Issue 7 (July 2020) - Curto, Hugo; Thuault, Anthony; Jean, Florian; Violier, Maxence; Dupont, Vedi; Hornez, Jean-Christophe; Leriche, Anne
Abstract: In this paper, a quick and efficient route to produce complex-shape alumina is reported. Alumina pieces are shaped by additive manufacturing (stereolithography) and densified by microwave sintering. Two raw powders are investigated in terms of both printing and microwave sintering: one alumina grade appropriate for additive manufacturing but not for microwave sintering, and vice-versa for the other grade. The mixture of the two raw powders allows both stereolithography printing and microwave sintering. Alumina parts processed by additive manufacturing followed by microwave sintering were successfully prepared and exhibited relative densities of about 93%, elastic modulus up to 236 GPa and Vickers hardness up to 12 GPa. Notwithstanding the part properties, the as-proposed coupling resulted in a time saving of 30%.